Changes in Medical Management after Coronary CT Angiography - Naue,Vânia Mairi (2015)
AbstractIntroduction:Coronary computed tomography angiography (CCTA) allows for non-invasive coronary artery disease (CAD) phenotyping. There are still some uncertainties regarding the impact this knowledge has on the clinical care of patients.Objective:To determine whether CAD phenotyping by CCTA influences clinical decision making by the prescription of cardiovascular drugs and their impact on non-LDL cholesterol (NLDLC) levels.Methods:We analysed consecutive patients from 2008 to 2011 submitted to CCTA without previous diagnosis of CAD that had two serial measures of NLDLC, one up to 3 months before CCTA and the second from 3 to 6 months after.Results:A total of 97 patients were included, of which 69% were men, mean age 64 ± 12 years. CCTA revealed that 18 (18%) patients had no CAD, 38 (39%) had non-obstructive (< 50%) lesions and 41 (42%) had at least one obstructive ≥ 50% lesion. NLDLC was similar at baseline between the grups (138 ± 52 mg/dL vs. 135 ± 42 mg/dL vs. 131 ± 44 mg/dL, respectively, p = 0.32). We found significative reduction in NLDLC among patients with obstrctive lesions (-18%, p = 0.001). We also found a positive relationship between clinical treatment intensification with aspirin and cholesterol reducing drugs and the severity of CAD.Conclusion:Our data suggest that CCTA results were used for cardiovascular clinical treatment titration, with especial intensification seen in patients with obstructive ≥50% CAD.